Adherence to iron supplementation amongst pregnant mothers in Surabaya, Indonesia: Perceived benefits, barriers and family support - Mira Triharini; Nursalam; Agus Sulistyono; Merryana Adriani; Ni Ketut Alit Armini; Aria Aulia Nastiti (Elsevier, 2018)
Background: Anaemia during pregnancy is a major nutritional problem that can cause preterm delivery and low birth weight. Adherence to iron supplementation can prevent anaemia during pregnancy. However, adherence to iron supplementation remains a problem in many countries. Objective: This study aimed to identify the correlations of the perceived benefits and perceived barriers of and family support for iron supplementation with adherence to this practice amongst pregnant woman in Surabaya, Indonesia. Methods: A cross-sectional study was carried out on 102 pregnant women who attended check-ups at the Puskesmas and received iron supplementation. Data were collected using questionnaires. Results: Perceived benefits (r = 0.334, P = 0.001), perceived barriers (r = −0.294, P = 0.003) and family support (r = 0.263, P = 0.008) were noted to be correlated with adherence to iron supplementation amongst pregnant woman in Surabaya, Indonesia. Conclusion: Perceived benefits, perceived barriers and family support are related to adherence to iron supplementation; thus, developing good perceptions and family support should be properly promoted. Keywords: Adherence, Anaemia, Family support, Iron, Pregnancy